Impact assessment of land use and cover changes on water resources using RS and GIS Techniques in watershed area - MAKWANA, JAYDIP J.; TIWARI, MUKESH K.; PAMPANIYA, N. K. (Journal of Soil and Water Conservation, 2020)
Management, assessment and simulation of different water resource variables are important at watershed scale to understand their interactions for appropriate water resource planning and management. The advent and recent development of RS and GIS techniques has facilitated the generation of spatially temporally distributed information very accurately, precisely and in an very time efficient manner that makes it possible to apply physically based hydrologic models for water resource variables simulation in a simply and realistically manner as possible. In present study, the effect of land use and land cover changes in the hydrologic response of a watershed is assessed for different rainfall events on surface, sub-surface and groundwater recharge, along with infiltration and evapotranspiration losses using widely recognised SWAT model in a watershed with limited gauges and data availability. Two different years of land use maps representing a 12 years of period, in which the area underwent a significant land use transition, were applied to the SWAT hydrological model to see the effect of land use change on hydrological response in the watershed. The SWAT model was calibrated and validated during the period of 2009-2010 and 2011-2012, respectively. The higher runoff rate and volume produced during validation period by SWAT with LISS-III is due to increased agricultural land and decreased forest land, whereas SWAT with LANDSAT ETM+ model shows that the same event could have produced lower runoff compared to runoff obtained in 2011-2012. Based on different performance indices, it was found that SWAT model coupled with the capabilities of RS and GIS performs good during both calibration and validation periods in Limkheda watershed.